Thrombosed native hemodialysis fistulas: Technical and clinical outcomes of endovascular recanalization and factors influencing patency. Issue 6 (November 2019) - So, Young Ho; Choi, Young Ho; Oh, Sohee; Jung, In Mok; Chung, Jung Kee; Lucatelli, Pierleone
Purpose: To evaluate the technical and clinical results of endovascular recanalization of thrombosed native hemodialysis fistula and the factors influencing patency. Methods: A retrospective study was conducted with 73 patients who had thrombosed arteriovenous fistulas and were treated with endovascular methods. Patient characteristics, arteriovenous fistula-related characteristics, and endovascular procedures were analyzed. Technical and clinical results and patency rates were evaluated. The factors influencing patency were analyzed using a univariate and multivariate Cox proportional hazards model. Results: Technical and clinical success rates were 93% (68/73) and 85% (62/73), respectively. At 3, 6, and 12 months, the primary patency rates were 87.9%, 73.3%, and 64.8%; assisted primary patency rates were 89.2%, 78.6%, and 70.7%; and secondary patency rates were 90.8%, 87.2%, and 83.1%, respectively. Previous intervention and cephalic arch stenosis were risk factors for lower primary and assisted primary patency ( p  < 0.05 for all). Cephalic arch stenosis was the only risk factor for lower secondary patency ( p  < 0.05). No major complications associated with the procedures were noticed. Conclusion: Endovascular treatment was effective for the immediate recanalization of thrombosed arteriovenous fistula. In addition, previous intervention and cephalic arch stenosis were significantly related to lower arteriovenous fistula patency.